An Account of the English Colony in New South Wales, Volume 1 : With Remarks on the Dispositions, Customs, Manners, Etc. of The Native Inhabitants of That Country. to Which Are Added, Some Particulars of New Zealand; Compiled, By Permission, From The Mss. of Lieutenant-Governor King. - Collins, David, 1756-1810; King, Philip Gidley, 1758-1808 (Salt Lake City, UT : Project Gutenberg, 2004)
"An Account of the English Colony in New South Wales, Volume 1" by David Collins is a historical account written in the late 18th century. The work provides a detailed narrative of the establishment and early years of the English penal colony at New South Wales, exploring the hardships faced by the convicts and settlers as well as their interactions with the local Indigenous populations. The opening of the book introduces the initial preparations for the colony, beginning with a description of the convicts who are to be transported to Botany Bay, their experiences aboard the ships, and the challenges faced during the voyage. Collins outlines the organization of the fleet, detailing the different vessels involved and the arrangements made for the safety and well-being of the convicts during their passage. By setting the stage for the arrival in New South Wales, the opening sets the tone for a comprehensive exploration of the colony's early struggles, governance, and the intricate dynamics with the Indigenous inhabitants, effectively framing the historical narrative to follow. (This is an automatically generated summary.)
Release date is 2004-06-01
Produced by Col Choat
Keywords: New South Wales -- Description and travel